Acquired hemorrhagic coagulopathy due to contact with the rodenticide brodifacoum in the Nutcracker bait - V V Voĭtsekhovskiĭ; A V Pivnik; L G Bitiutskaia; T T Protsko (Терапевтический архив, 2012)
Rodenticide (RD) application is the most effective chemical procedure against rodents. RDs containing indirect-action anticoagulants have received currently wide acceptance. When the recommended standards for handling these agents and precautionary measures in their use are violated, there may be poisoning, the main manifestation of which is hemorrhagic coagulation. The paper provides a literature review on poisoning by RDs having anticoagulant properties. This communication gives a detailed description of a clinical case of poisoning with brodifacoum contained in the ready-to-use Nutcracker bait due to long-term exposure to the rat poison that has a cumulative effect. Careful history data collection and coagulogram analysis make it possible to establish a correct clinical diagnosis and to use appropriate therapy that leads to patient recovery.